A dual-voltage electronic megger / Mohd Shamsol Bahri Abdul Aziz, Mohd Yusri Mohd Yusop and Sulaiman Abdul Majid - Abdul Aziz, Mohd Shamsol Bahri; Mohd Yusop, Mohd Yusri; Abdul Majid, Sulaiman (1990)
Megaohmeter or better known as meger is an important Measuring instrument in Electrical Power, especially for insulation testing. First there was an insulation tester, a hand driven type, incorporating a built-in generator and a constant DC voltage circuit to provide a stable output. Then there was the electronic or transistorised type megger which uses electronic circuit and batteries to supply the power. The basic concept of the hand driven type and the electronic or transistorised type megger is the same. Both types of megger only Measure at a single voltage.